Polycyclic aromatic hydrocarbons in sediments and fish species from the White Nile, East Africa: Bioaccumulation potential, source apportionment, ecological and health risk assessment - Abayi, Juma John Moses; Tombe Gore, Christopher; Nagawa, Christine; Bandowe, Benjamin A.Musa; Matovu, Henry; Mubiru, Edward; Chelangat Ngeno, Emily; Odongo, Silver; Sillanpaa, Mika; Ssebugere, Patrick (Environmental Pollution, 2021)
The impact of oil exploration and production activities on the environment of sub-saharan African countries is not well studied. This study aimed at determining concentrations, sources, and bioaccumulation of 13 polycyclic aromatic hydrocarbons (PAHs) in sediments and fish from the White Nile near Melut oil fields, South Sudan. The study also assessed the ecological and human health risk associated with PAHs in this aquatic system. Total ( P 13) PAH concentrations ranged from 566 to 674 ng g 1dry weight (dw) in sediments, while those in fish were 191e1143 ng g 1 wet weight (ww). P 13PAH concentrations were significantly higher in C. gariepinus than in other fish species. Low molecular weight PAHs (LPAHs) dominated the profile of PAHs in sediments (constituted 95% of P P 13PAHs) and fish (97% of 13PAHs). Compared to Sediment Quality Guidelines of the United States Oceanic and Atmospheric Administration, the levels of LPAHs in this study were all above the threshold effect limits, but below the probable effect level, while those of high molecular weight PAHs (HPAHs) were all below the lowest effect levels. The carcinogenic potency equivalent concentrations of PAHs in L. niloticus and C. gariepinus were above the US EPA screening level; suggesting consumption of these species could adversely affect human health. Biota-sediment accumulation factor values (range: 0.006e3.816 g OC g 1 lipid) for PAHs showed high bioaccumulation of LPAHs in fish muscle, and that bioaccumulation decreased with increase in hydrophobicity of the compounds. This is possibly because LPAHs have higher aqueous solubilities which increases their bioavailability through water-gill transfers compared to HPAHs. Profiles of PAHs in the White Nile environment indicate predominant contribution from petrogenic sources, which could be attributed to presence of crude oil reservoirs and oil production operations. More research into the levels of other environmental pollutants in the oil-rich area is recommended.
Keywords: Polycyclic aromatic hydrocarbons; Cancer risk; Bioaccumulation; Ecological risk